La Tragédie du vengeur de Thomas Middleton, ou la thérapie paradoxale du théâtre - Elodie Likhtart (Etudes Epistémè)
The Revenger’s Tragedy, by T. Middleton, is similar to many other revenge tragedies insofar as the main protagonist aims to punish the authors of crimes committed against himself and/or his kin. In this tragedy, however, the play’s audience witnesses both the revenger’s will to act for personal reasons and his desire to purify society as a whole. To attain these goals, he implements various therapies which are sometimes similar to the puritans’ strategies, yet at other times totally opposed to them. It is the intertwining of the opposing aspects of this puritan-avenger which forms the paradox.